Imprecision in Accounting Measurement: Can It Be Value Enhancing? - KANODIA, CHANDRA; SINGH, RAJDEEP; SPERO, ANDREW E. (Journal of Accounting Research, 2005)
Accounting measurements of firms' investments are usually imprecise. We study the economic consequences of such imprecision when it interacts with information asymmetry regarding an investment project's ex ante profitability, known only by the firm's managers. Absent agency and risk-sharing considerations, we find that some degree of accounting imprecision could actually be value enhancing. We characterize the optimal degree of imprecision and identify its key determinants. The greater the information asymmetry regarding the project's profitability, the greater is the imprecision that should be tolerated in the measurement of the firm's investment.